2023
DOI: 10.5455/javar.2023.j660
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Leucaena and molasses can increase the nutritional quality and rumen degradation of corn stover silage

Abstract: Objective: The study was conducted to determine the effect of Leucaena at different proportions and doses of molasses on the nutritional quality, silage fermentation characteristic, and in vitro digestibility of corn stover silage. Materials and Methods: The study was designed in a completely randomized factorial design 3*3 pattern. The first factor was the proportion addition of Leucaena, i.e., L0 (0%), L15 (15%), L30 (30%), and L45 (45%) of inclusion of Leucaena on the dry matter (DM) basis of corn stover. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…This means that other nutrients present in the diet might have influenced the degradability of starch in the rumen. Sutaryono et al [ 96 ] reported that the inclusion of Leucaena in corn stover silage affected DMD and OMD in the in vitro study. This is due to the fact that cellulose is more resistant to digestion compared to starches [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that other nutrients present in the diet might have influenced the degradability of starch in the rumen. Sutaryono et al [ 96 ] reported that the inclusion of Leucaena in corn stover silage affected DMD and OMD in the in vitro study. This is due to the fact that cellulose is more resistant to digestion compared to starches [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…tarramba) has the advantage of being resistant to psyllid bug pest and resistant to dry seasons (Y. Sutaryono et al, 2023).…”
Section: Botanical Composition Of Cattle Forage Plantsmentioning
confidence: 99%
“…They know that giving lamtoro feed plants can accelerate the growth of cows compared to grass feed, so the average breeder on the island of Sumbawa uses lamtoro as a basis for cattle feed . Sutaryono et al (2023) states that the ideal botanical composition consists of 60% grass and 40% legumes, further Tahuk et al (2021) explained that legumes have a very important role in the use of feed as the main source of forage for livestock, because it can increase the nutritional value of the forage given. Thus the quality of crops/feed for cattle on Sumbawa Island is high, because the type of feed that dominates the total proportion of legumes, namely lamtoro is 46.16%.…”
Section: Botanical Composition Of Cattle Forage Plantsmentioning
confidence: 99%
“…Fermentation inhibitors are a category of additives that serve to enhance acidity, lower the pH of silage, and impede the proliferation of undesirable microorganisms, commonly including inorganic substances (aldehydes, salts and acid–base substances) and organic acids (formic acid, acetic acid, citric acid, malic acid) ( Queiroz et al, 2018 ). Research showed that the addition of molasses improved the fermentation quality of silage and reduced the breakdown of protein ( Sutaryono et al, 2023 ). Sorbic acid addition significantly improved fermentation quality and aerobic stability of rice straw silage, slowing down the reduction of lactic and acetic acids content as well as the growth of yeasts and aerobic bacteria under aerobic exposure ( Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%